Implementation Of TVSekolah Virtual Class in It Competency Transformation for PAUD Teachers - Niken Kurnia Ningsih; cut rosmawati; marwah marwah; Sri Watini (International Conferences on Early Childhood Education Proceedings, 2023)
Abstract The development of information and communication technology is so fast and influential in the world of education. This requires educators, especially teachers of Early Childhood Education to be able to adapt properly, professionally, creatively and innovatively. The role of digital technology that is currently developing is very influential in supporting the learning process, such as facilitating student interaction in learning at school, at home or anywhere, anytime, anywhere and with anyone. through TVSekolah virtual class-based learning with the hope of increasing the enthusiasm of teachers to be more creative, innovative in their work to develop their profession professionally. Therefore this research was conducted in order to describe the implementation of TVSekolah Virtual Classes in the Transformation of IT Competency of Early Childhood Education Teachers. This research method uses descriptive qualitative research where data collection techniques are through interviews, observation, and documentation. From the results of this study it can be concluded that with the implementation of the TVSekolah Virtual Classroom it can develop the IT Competence of Early Childhood Education Teachers in developing learning strategies or methods, from the preparation, implementation, and evaluation stages. With the ability to develop TVSekolah virtual classs will produce professional educators, ready to work, competitive, well versed in IT in the context of transforming teacher competencies, especially early childhood education teachers.